2019
DOI: 10.1007/s00192-019-04202-6
|View full text |Cite
|
Sign up to set email alerts
|

“Voice your choice”: a study of women’s choice of surgery for primary stress urinary incontinence

Abstract: Introduction and hypothesis This was an observational study aiming to determine factors which influence women's choice of surgery for primary stress urinary incontinence (SUI). Methods Two hundred twelve women undergoing a primary SUI procedure were recruited to this study from 12 hospitals in the north of England. After choosing a procedure, women were asked to complete a standardized semi-structured questionnaire about their health, demographics and a free text box to record factors important to them when ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 4 publications
0
11
0
Order By: Relevance
“…It has been reported that patient concern about polypropylene mesh and the media's representation of mesh procedures are key factors in women's decision making. This likely explains why a significant proportion of our patients have a negative preconception of synthetic MUS 19 …”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…It has been reported that patient concern about polypropylene mesh and the media's representation of mesh procedures are key factors in women's decision making. This likely explains why a significant proportion of our patients have a negative preconception of synthetic MUS 19 …”
Section: Discussionmentioning
confidence: 91%
“…This likely explains why a significant proportion of our patients have a negative preconception of synthetic MUS. 19 The mesh debate has significantly increased patient consultation times. There is evidence in literature that "consultation content" rather than "consultation length" positively impacts patient satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…The most used surgical intervention for female SUI is the Mid-Urethral Sling (MUS). 2 With the recent safety concerns and suggested underestimation of complications associated with MUS procedures, [3][4][5] there is a growing demand from both patients and physicians for less invasive treatment options with lower risk of complications. Moreover, when asking patients what they expect or prefer from a SUI treatment, this often differs from the physician's perception of success.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas physicians often look for a long-term solution or cure, patients are often looking for minimally invasive procedures providing relief and reduced impact on their quality of life. [4][5][6] In this retrospective study we analyzed the effectiveness and safety of a new procedure for the treatment of mild-tomoderate SUI using a bioresorbable and collagen-stimulating injectable based on polycaprolactone. Moreover, we describe a small adjustment to the standard 3-point injection technique commonly used, which in our experience that enhances effectiveness.…”
Section: Introductionmentioning
confidence: 99%
“…However, mesh complications, such as erosion, obstruction and pain [8], have raised concerns, and in England the new NICE Guidelines advise that midurethral slings only be considered if other procedures are not suitable [9]. Furthermore, studies have shown that women are prepared to trade efficacy for safety by preferring a minimally invasive procedure [10,11].…”
Section: Introductionmentioning
confidence: 99%